(untitled) (GIST – Education and Learning Research Journal, 2023)
Willingness to communicate (WTC) can enhance English as a foreign language (EFL) students’ English, so it has become a significant research topic. In the literature, there are several studies conducted on the reasons which can affect EFL students’ WTC. Yet, to the researchers’ best knowledge, little has been known about what EFL students suggest doing to maintain their WTC in online English language lessons. Therefore, the present study aimed to find out EFL students’ suggestions to maintain their WTC in online English language lessons. It was designed as a qualitative case study. 40 Turkish EFL students participated in the present study. The data were collected through an open-ended question and content analyzed. The findings of the present indicated that EFL students made several lesson-, topic-, activity-, teacher-, class-, assignment-, and program-related suggestions. The findings were discussed, the limitations of the study were explained, and suggestions for further studies were made.